Enhancing Students’ Reading Comprehension Quality Using the Jigsaw Method: A Case Study of Students in Universities - Suryanti; Jefriyanto Saud; M. Syahrul Izomi; Saepulloh; Ahmad Hariyadi (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This study explored the enhancement of students' reading comprehension in language learning through the application of the Jigsaw method in university environments. Employing a qualitative research approach, data regarding the improvement of students' reading comprehension quality were gathered from students enrolled at Muhammadiyah Bhuton University, Gorontalo State University, and Muhammadiyah Mataram University. Data collection utilized the observe-participant conversation method, wherein the researcher observed the enhancement of students' reading abilities across multiple campuses. Additionally, interviews with students and lecturers were conducted to investigate research problems, with recording and note-taking techniques employed to ensure data accuracy. Reflective introspective methods were further employed, engaging both the researcher and informants in discourse based on their respective experiences. The collected data underwent reduction, classification, and verification based on their types. Subsequently, the data were tabulated through the assignment of codes to each piece of information, followed by interpretation. The research findings revealed that the improvement of students' reading abilities in Indonesian language courses at Muhammadiyah Bhuton University progressed smoothly and effectively. Furthermore, the enhancement of Arabic language reading abilities at Muhammadiyah Mataram University was broader and more intensive, while the improvement of English language reading abilities at Gorontalo State University contributed to enhanced comprehension of English texts. The practical implications of these findings suggest that cooperative approaches like the Jigsaw method can serve as effective alternatives for enhancing students' reading comprehension abilities in university settings